Impact of community neonatal services: a multicentre survey. Issue 3 (1st November 2002) - Langley, D; Hollis, S; Friede, T; MacGregor, D; Gatrell, A
Abstract : Objectives: To explore the impact of a community neonatal service on high risk infant survivors in the first year of life. Design: Retrospective multicentre survey. Postal questionnaires were sent to selected parents. Setting: Thirty two neonatal units in England and Wales. Patients: Inclusion criteria: infants over 12 months of age with birth weight ≤1500 g, or who received level I intensive care for at least 48 hours. Exclusion criteria: multiple births, infants who had died or had severe congenital abnormalities. A total of 3367 eligible infants were selected, and their parents were sent a questionnaire; 65% responded. Main outcome measures: Length of stay on the neonatal unit from birth to initial discharge. Readmission to hospital during the first year of life. Results: The median length of stay in units with a community neonatal service was 35 days compared with 37 days in units without. When adjusted for infant and parent characteristics, the median length of stay was reduced by 12.6% where a community neonatal service was provided (95% confidence interval 5.3% to 19.3%). The readmission rates were 44.6% in units with a community neonatal service and 43.5% in units without. There was no significant reduction in the adjusted odds of readmission. Conclusions: The retrospective nature of this study means that these findings cannot be definitely attributed to the presence of a community neonatal service. However, the results suggest that community neonatal services may reduce the length of stay without any subsequent increase in readmission.